Peran Mindfulness dalam Meningkatkan Spiritualitas dan Praktik Keagamaan Umat Buddha di Kota Medan - Fitriani Fitriani; Elly Warnisyah Harahap; Amroeni Drajat (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2026)
The modern era is characterized by rapid urbanization, secularization, and materialism in large cities such as Medan, which have created significant spiritual challenges for Buddhist communities. The pressures of multicultural urban life often erode the depth of religious practice and the connection with the transcendent dimension. This study examines the role of mindfulness as a relevant approach to revitalizing the spirituality and religious practices of Buddhists in Medan by integrating full awareness rooted in Buddhist traditions, particularly the Satipatthana Sutta, Vipassana, and Samatha. This research employs a qualitative method based on library research. Data were collected from primary sources such as the Tipitaka, Suttas, and classical Buddhist literature, as well as secondary sources including scientific journals, vihara activity reports (such as those from Vihara Borobudur and Maha Vihara Maitreya), and empirical studies on mindfulness in Indonesia. The analysis was conducted using thematic content analysis, hermeneutic interpretation, and comparative approaches. The discussion reveals that mindfulness is practiced through mindful breathing, mindful eating, and the Day of Mindfulness programs held at various viharas in Medan. These practices strengthen meditation discipline, reduce dukkha (suffering), enhance equanimity, and build mental resilience amid urban dynamics. However, their implementation faces challenges, including resistance from traditionalist groups who are concerned about the simplification of teachings and the separation of sati from the core Buddhist framework of sila (ethics), samadhi (concentration), and panna (wisdom), as well as accessibility issues for the community. The study concludes that mindfulness has strong potential to serve as an effective bridge between classical Mahayana traditions and the needs of modern urban society in Medan, provided it is implemented in an integrative manner that does not undermine the essence of Buddhist teachings.